2019
DOI: 10.1002/ejsp.2620
|View full text |Cite
|
Sign up to set email alerts
|

The more you have, the more you want? Higher social class predicts a greater desire for wealth and status

Abstract: Traditional theories have focused on the intentions of lower‐class individuals to climb on the social ladder, yet they have paid relatively little attention to the motivations of upper‐class individuals to ascend even higher. Addressing this issue, Studies 1 and 2 provided cross‐national evidence that higher social class is associated with a greater desire for wealth and status. Moreover, by manipulating perceived social class, Studies 3 and 5 experimentally confirmed that compared to people in the lower‐class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 55 publications
(90 reference statements)
2
37
0
Order By: Relevance
“…1: Relation between the socio-structural context and strategies used by the wealthy when responding to minorities (adapted and amended from dissatisfaction with not climbing fast enough may lead to lashing out at those who are more vulnerable in society (i.e., minorities). In particular, Wang et al (2018) showed evidence for this "having morewanting more" effect in a series of cross-sectional and experimental studies where they found that compared to people in a lower wealth group, those in a higher wealth group expressed a stronger desire for wealth and status. There is initial evidence that the wish to gain more wealth and status is particularly pronounced among those who are wealthier (Wang et al, 2018).…”
Section: Permeability Of Boundaries: Upward Mobility Pressurementioning
confidence: 99%
See 4 more Smart Citations
“…1: Relation between the socio-structural context and strategies used by the wealthy when responding to minorities (adapted and amended from dissatisfaction with not climbing fast enough may lead to lashing out at those who are more vulnerable in society (i.e., minorities). In particular, Wang et al (2018) showed evidence for this "having morewanting more" effect in a series of cross-sectional and experimental studies where they found that compared to people in a lower wealth group, those in a higher wealth group expressed a stronger desire for wealth and status. There is initial evidence that the wish to gain more wealth and status is particularly pronounced among those who are wealthier (Wang et al, 2018).…”
Section: Permeability Of Boundaries: Upward Mobility Pressurementioning
confidence: 99%
“…While status and power are by definition conferred by others, wealth is solely based on the possession of financial and material resources relative to others (Wang, Jetten, & Steffens, 2018). While status and power are by definition conferred by others, wealth is solely based on the possession of financial and material resources relative to others (Wang, Jetten, & Steffens, 2018).…”
Section: Setting An Agendamentioning
confidence: 99%
See 3 more Smart Citations